KONSEP KAFĀ’AH DALAM KEHARMONISAN RUMAH TANGGA : PRESPEKTIF HADITS KITAB NAIL AL-AUTHAR - Azmi , Fadli (Khulasah : Islamic Studies Journal, 2024)
Kafā’ah in marriage is to avoid the occurrence of crisis in the household, and with the presence of kafā’ah or harmony in marriage is expected to be able to get harmony and harmony in running the household wheel.Marriage is a universal and universal law for all creatures., Good for humans, and animals and plants., And a way chosen by Allah swt as a way for his creatures to multiply., and preserving his life..Marriage will play a role once each partner is ready to play its positive role in realizing the purpose of the marriage itself . Including in the case of kafa ah.Husband and wife should be able to actualize it in building household harmony, So that the marriage is settled., The Merciful One.. This book is a book about the study of the Bible.. To find the concept of kafā’ah in hadiths perspective hadiths in the book nail al-authar of al syauqani.The results of this study have found the concept of kafa ah in the household harmony perspective of the book of nail al-authar namely: 1.No marriage or no marriage, 2 The Nassau, 3 The Religion and the Fourth.Social status. The purpose of the marriage is to bring about a marriage., But Ka'bah is not an absolute condition., But kafā’ah can be the main sponsor, In the case of religion and good manners..Marriage that does not pay attention to the concept of kafā’ah, Then the family will have trouble adapting to each other., Complementing each other, Love each other, They respect each other And mutual understanding.For that reason, to be used as the basis of congruity implemented in forming a harmonious households.